Asuhan Keperawatan Pada Anak Dengan Demam Berdarah Dengue - Sarah Tsabitha Natasha Bella; Siti Nurhayati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
Dengue hemorrhagic fever (DHF) is an acute epidemic disease caused by a virus transmitted by the Aedes aegypti and Aedes albopictus. Dengue hemorrhagic fever (DHF) is infectious disease caused by dengue virus with some symptoms include fever, joint and muscle pain, rash, trombhocytopenia and bleeding diathesis. The purpose of writing is that students are expected to get real-life experiences to provide nursing care for children with DHF. The methods of writing are descriptive and literature. The result of the scientific paper is that students get an overview of nursing care in children with DHF. The nursing diagnosis in case of An.A: Risk of fluid volume deficit, Imbalance of nutrients less than body requirements, Risk of bleeding and anxiety.